Dental Professionals’ Attitude towards Provision of Removable Partial Denture in Pakistan - Abdul Rehman, Sajjad Hussain, Moiza Ijaz, Haider Iqbal, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: With the advancement in technology and availability of better treatment modalities for rehabilitation of partially dentate patients, the use of cast partial denture in clinical practice as well as in teaching curriculum has been declined. Objective: To know the perspective of dental professionals towards provision of cast partial dentures in Pakistan Study Design: Cross-sectional survey Place and Duration of Study: Margalla Institute of Health Sciences, Rawalpindi from 1st January 2023 to 30th June 2023. Methodology: Two hundred and five responders were enrolled through survey included eight closed ended questions regarding use of cast partial dentures and shared via emails to dental processionals practicing in Pakistan. Results: Majority of the dental professionals (38.5%) preferred fixed partial dentures as choice of rehabilitation for partially dentate arches, whereas consultants preferred implants. Among the various types of removable partial dentures, the most preferred choice was cast partial dentures (52.2%), and the least preferred choice was flexible RPD (10.7%). Majority of the dental practitioners (42.4%) reported a cost issue followed by difficulty in adjustment (31.7%) while suggesting cast partial dentures. Although high numbers of dentists (58%) are in favor of implant supported prosthesis or better treatment options compared to cast partial dentures, still (62.0%) of dentists supported that more importance should be given to cast partial dentures in undergraduate curriculum. Conclusions: Majority of the dentists in Pakistan prefers fixed partial denture for rehabilitation of partially edentulous arches, consultants were in favour of implants. If given choices in removable partial dentures, most of dentists like cast partial dentures but avoid in clinical practice due to availability of better treatment options, high cost, and complicated procedures. Keywords: Attitude, Dental professionals, Cast partial denture, Curriculum.